Dandyism in the work of Oscar Wilde - Kaválková, Petra (Univerzita Pardubice, 2018)
This work focuses on the signs of Dandyism in the literary works of Oscar Wilde and his own life. The theoretical part serves as an introduction to the topic of Dandyism in relation to Aestheticism, Decadence and the Victorian society. The analytical part focuses on the core features of a Dandy in more detail, which are then shown on Wilde's characters that indicate them, while discussing whether such characters can be considered true Dandies. Wilde's own life is compared to these instances as well.
Aspekty dandysmu v díle Oscara Wildea
Keywords: Wilde, Oscar; dandyism; aestheticism; decadence; Victorian society; hedonism; Wilde, Oscar; dandysmus; esteticismus; dekadence; viktoriánská společnost; hédonismus